Teaching tech together : how to make lessons that work and build a teaching community around them - Wilson, Greg, 1963- (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
"Hundreds of grassroots groups have sprung up around the world to teach programming, web design, robotics, and other skills outside traditional classrooms. These groups exist so that people don't have to learn these things on their own, but ironically, their founders and instructors are often teaching themselves how to teach. There's a better way. This book presents evidence-based practices that will help you create and deliver lessons that work and build a teaching community around them. Topics include the differences between different kinds of learners, diagnosing and correcting misunderstandings, teaching as a performance art, what motivates and demotivates adult learners, how to be a good ally, fostering a healthy community, getting the word out, and building alliances with like-minded groups. The book includes over a hundred exercises that can be done individually or in groups, over 350 references, and a glossary to help you navigate educational jargon"--
Includes bibliographical references (pages 169-210) and index.
CSE
Keywords: Computer programming -- Study and teaching; Web sites -- Design -- Study and teaching; Robotics -- Study and teaching